Wyoming strong - Palmer, Diana (Palmer, Diana. Wyoming men series., 2014)
When fate intervenes and brings them together on neighboring Wyoming ranches, archenemies Wolf Patterson and Sara Brandon cast their differences aside when they see each other in a whole new light as love takes root between them.